The Relationship between Resilience & Mental Health among a Sample of University of Nizwa Students - Sultanate of Oman - Rudwan, Samer; Alhashimia, Saada (European Scientific Journal, ESJ, 2018)
This study employs the descriptive approach to identify the relationship between resilience and mental health in light of some variables in a student sample at the University of Nisswa. The sample consisted of 1,000 students, including 403 men and (597) women. The sample random sampling. Two instruments were used: the resilience scale (Connor & Davidson , 2003) and the Arab Mental Health Scale (Abdel-Khalek, 2011). The psychometric properties of both scales were tested. To answer the study questions, the following statistics were used: Pearson correlation coefficient, t-test, one-way ANOVA Test, LSD test, and regression analysis. The results indicate a positive correlation between mental health and resilience. There was also a significant difference between female and male students in terms of resilience and mental health in favor of female students; It seems that women are more resilient and healthier than men. The study of age differences did not reveal any differences. The study also indicates that resilience has a significant impact on mental health. Finally, the results were tweaked against the limitations of the study.